HERDABILIDADE E CORRELAÇÕES GENÉTICAS PARA CARACTERES AGRONÔMICOS EM GIRASSOL - Mattioni, Tânia C.; Schwertner, Diogo V.; Bandeira, Taiane P.; Silva, Adair J. d.; Matter, Edegar; Krüger, Cleusa A. M. B.; Fernandes, Sandra B. V.; Berto, Jorge L.; Garcia, Dagmar C.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo